2001
DOI: 10.1021/ja016465m
|View full text |Cite
|
Sign up to set email alerts
|

Electropolymerization of Pd(II) Complexes Containing Phosphinoterthiophene Ligands

Abstract: A series of Pd complexes of 3'-diphenylphosphino-2,2':5'2' '-terthiophene (1a, dppterth) in which the metal is coordinated in three different modes have been prepared and electropolymerized, resulting in the formation of conductive thin films. In [Pd2(mu-Cl2)(dppterth-P,C3)2] (3a) the metal is P,C-coordinated, in [PdCl2(dppterth-P)2] (4a) the coordination is monodentate via the phosphine, and in [Pd(dppterth-P,C3)(dppterth-P,S1)][PF6] (5a) both P,C- and P,S-coordination modes are found. In 5a, the coordinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 56 publications
4
53
0
Order By: Relevance
“…To demonstrate the power of the new regioselective methods, they were applied to the synthesis of the known compound 4Ј-bromo-5-methyl-2,2Ј;5Ј,2"-terthiophene (16) [20] from thiophene (Scheme 1). By the new methods, the total number of steps was reduced from six to three, and the overall yield increased from 15 to 43 %.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the power of the new regioselective methods, they were applied to the synthesis of the known compound 4Ј-bromo-5-methyl-2,2Ј;5Ј,2"-terthiophene (16) [20] from thiophene (Scheme 1). By the new methods, the total number of steps was reduced from six to three, and the overall yield increased from 15 to 43 %.…”
Section: Resultsmentioning
confidence: 99%
“…395,396 The presence of cis-and trans-isomers has been comfirmed from 31 P NMR specroscopy. Electropolymerization of these complexes showed large electronic interactions between Pd moieties and the polythiophene backbone, which produced an increase in conductivity of the polymer film.…”
Section: Other Ligand-functionalized Oligothiophenesmentioning
confidence: 89%
“…These bond lengths are comparable to those which are previously reported in other complexes of this type. 11 The C-S bond lengths are not equal in oligothiophene due to coordination of two rings with P atom at one α-position. It has also been suggested that enhanced π-back bonding with coordinated thiophene ring would weaken the C-S bond.…”
mentioning
confidence: 99%